(untitled) (Applied Biological Research, 2023)
B-type natriuretic peptide (BNP) is a highly sensitive and specific indicator of the size of myocardial infarction, which can help in assessing the degree of cardiovascular risk. Elevated BNP levels in patients hospitalized for acute myocardial infarction (AMI) are associated with heart failure and mortality, and the measurements of BNP in a short-term period could be helpful to predict the future events. The role of short-term follow-up BNP level has not been established in the patients with AMI. This retrospective study was conducted on the patients admitted to the Government Medical College, Jammu (India). The analysis of blood EDTA sample was analysed for BNP and this test was performed by using a fully automated random access immunoassay analyser whose principle is based on micro-particle enzyme immunoassay (MEIA). The reference range of BNP is 0-100 pg mL-1. The study revealed a 90% BNP increase in AMI patients in comparison to the 10% increase in normal healthy ones. However, BNP showed elevated levels in healthy individuals suffering from renal insufficiency. The BNP was > 100 pg mL-1in the majority of AMI patients while in controls BNP is <100 pg mL-1.